The characteristics and pattern of care for the type 2 diabetes mellitus population in the MENA region during Ramadan: An international prospective study (DAR-MENA T2DM). (May 2019) - Hassanein, Mohamed; Al Awadi, Fatheya F.; El Hadidy, Khaled El Sayed; Ali, Sobia Sabir; Echtay, Akram; Djaballah, Khier; Dessapt-Baradez, Cecile; Khazaal, Faris Abdul Kareem; Abu-Hijleh, Mohamad Omar; Al Shaikh, Abdulrahman; Gharbi, Mohamed El Hassan; Shehadeh, Naim; et al.
Highlights: Many Muslims with type 2 diabetes mellitus (T2DM) from MENA fast during Ramadan. Hypoglycemia remains a risk for Muslims with T2DM who choose to fast. Choice of diabetes therapy affects hypoglycemia risk during Ramadan fasting. Increased patient education is needed to reduce hypoglycemia risk. Dose adjustments and therapy change should be considered pre-Ramadan. Abstract: Aims: We aimed to describe the characteristics and care of participants with diabetes during Ramadan in the Middle East and North Africa (MENA). Methods: In this prospective, observational study, we analysed the number of fasted days, number of participants fasting, glycemic control, rate of hypoglycemic events, and lifestyle patterns for participants with T2DM during Ramadan 2016. Results: The population included 1749 participants with T2DM. The mean (SD) duration of fasting was 27.7 (5.0) days, and 57.3% of participants fasted for the full duration of Ramadan. Following Ramadan, a significant improvement in HbA1c, FPG, and PPG was observed (p < 0.0001). Confirmed hypoglycemia increased significantly from before to during Ramadan (incidence: 4.9% vs. 10.4%, p < 0.001; adverse events: 0.11 vs. 0.22 events/month/participant, p < 0.001) and was dependent on the treatment regimen. Severe hypoglycemia incidence was 0.2% before versus 0.9% during Ramadan (p = 0.031), whereas adverse events remained comparable (0.01 events/month/participant; p = 0.154). Most participants (97.4%) reported lifestyle changes during Ramadan. Conclusions: This prospective study is the first to describe the characteristics and care of participants with T2DM during Ramadan in MENA, and can be utilized in the development of evidence-based care to ensure the safety of participants who fast.